2016
DOI: 10.1111/jar.12268
|View full text |Cite
|
Sign up to set email alerts
|

Developing the personal narratives of children with complex communication needs associated with intellectual disabilities: What is the potential of Storysharing®?

Abstract: The Storysharing intervention appears to be associated with changes to the dyadic, personal narratives illustrating its potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Various classroom training studies involving narratives have already been successfully carried out with preschool non-TD children (e.g., [91,92]). In this regard, [92] demonstrated that narrative interventions are a promising and effective strategy to teach oral narration to children with risk factors and narrative language delays, who may benefit from it in terms of their short-term and longterm narrative retelling skills (see also [93][94][95][96]). We claim that more effective interventions should include training focused on not only children's speech but also their gestures and general multimodal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Various classroom training studies involving narratives have already been successfully carried out with preschool non-TD children (e.g., [91,92]). In this regard, [92] demonstrated that narrative interventions are a promising and effective strategy to teach oral narration to children with risk factors and narrative language delays, who may benefit from it in terms of their short-term and longterm narrative retelling skills (see also [93][94][95][96]). We claim that more effective interventions should include training focused on not only children's speech but also their gestures and general multimodal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of obtained results suggest that speech impairments produce a negative effect on forecasting formation that further can lead to deviations in behavior in this category of children; the works of Sreckovic, Hume, and Able (2017); Mrachko and Kaczmarek (2017); Marshall, Harding, and Roulstone (2017); Sylvestre, Brisson, Lepage, Nadeau, and Deaudelin (2016); Bunning et al (2013); Bunning, Gooch, and Johnson (2017) prove this conclusion.…”
Section: Discussionmentioning
confidence: 84%
“…The current study contributes to the evidence base of narrative interventions for people with intellectual disability that included fewer participants or no control group (e.g. Bunning et al., 2017; Cloitre & Beck, 2017; Fredman, 2014; Gonçalves et al, 2016; Grove, 2015; McParland, 2015; Peterson, Gillam, Spencer, & Gillam, 2010). It also adds to the evidence base of well‐defined interventions specifically developed for people with intellectual disability and psychiatric symptoms (Ali, Hall, Blickwedel, & Hassiotis, 2015; Kok, van der Waa, Klip, & Staal, 2016; McCabe, McGillivray, & Newton, 2006; Osugo & Cooper, 2016; Shepherd & Beail, 2017; Vlissides et al., 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Life story interventions for persons with intellectual disability have attracted growing interest and appreciation in recent years, sometimes also in combination with mental health problems (e.g. Bunning, Gooch, & Johnson, 2017; Cloitre & Beck, 2017; Gonçalves, Machado, Martins, Hoek, & Machado, 2016; Grove, 2015; McParland, 2015). The self‐reported life stories of people with intellectual disability and psychiatric symptoms often pay little attention to their qualities, values, capabilities and talents.…”
Section: Introductionmentioning
confidence: 99%